'In on the ground floor': Women and the early BBC television service, 1932–1939. (September 2022) - Murphy, Kate
This is a working paper on women and the early BBC television service, prior to September 1939. It considers women in four main areas of work: in production roles, in secretarial/clerical support work, in Makeup and Wardrobe, and as on-screen announcers. Apart from the latter two, which were developed especially for television, it shows a clear link with radio practices, particularly the possibility of women moving through the ranks. The paper argues that, had there not been a seven year hiatus for the Second World War, women would have reached elevated positions in the television service much sooner.